Charcterization of COVID-19 hospitalized adult patients, vaccinated vs non-vaccinated in Duhok province - Abdulsalam Mohammed , Paiman; Aghali Merza , Muayad (Journal of Contemporary Medical Sciences, 2022)
Objectives: First, to determine prevalence of vaccinated COVID-19 patients among hospitalized patients; Second, to determine the epidemiological, clinical, and laboratory characteristics of vaccinated and unvaccinated COVID-19 patients. Methods: The study was carried out on 300 adult COVID-19 hospitalized patients at Duhok COVID-19 health facilities. A prospective cross-sectional study was used as the study design. Between October 1, 2021, and March 31, 2022, all patients with PCR-confirmed COVID-19 were enrolled. Results: The majority of people in this study were unvaccinated. Pfizer was most popular among people who had received vaccination. The majority of hospitalized patients were old ages, the mean age was 60.73 ± 15.83 yr. In our study, the unvaccinated females had higher infection rates while vaccinated males had higher hospital admission rates. In our study, vaccinated patients had shorter hospital duration stays. In both vaccinated and unvaccinated patients, predominated cases were severe cases. D dimer was significantly higher among vaccinated patients. The mortality rate was relatively high among both groups. Patients who had received vaccinations tended to experience vomiting and flu-like symptoms more frequently than those who had not. In terms of comorbidities, smoking and malignancy were significant risk factors for COVID-19 infection in unvaccinated patients. Conclusion: We looked at 300 COVID-19 hospitalized patients. In this study, the majority of people were unvaccinated. Pfizer, had higher prevalence among vaccinated individuals. Majority were elderly. The unvaccinated cases had a higher rate of female hospital admissions than male. The D.Dimer level was significantly different between the two groups. Vomiting and flu-like illness showed higher prevalence in vaccinated cases with significant difference. Smoking and malignancy were significant risk factors for COVID-19 infection in unvaccinated patients. In the fight against a public health disaster like a COVID-19 pandemic, the availability of a COVID-19 vaccines campaign are crucial.